Nilai Perusahaan ditinjau dari aspek Manajemen Laba dan Pengungkapan Corporate Social Responsibility (CSR) - Nasrul Warid (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
One of the goals of establishing a company is to make various efforts to increase firm value so that it can provide prosperity for shareholders. There are various factors that can affect firm value, one of which is earnings management. In addition, the disclosure of corporate social responsibility (CSR) can also affect firm value. This study aims to determine the effect of earnings management and corporate social responsibility (CSR) on firm value. This research is a literature study that is sourced from theory and various relevant previous research journals. The results show that earnings management and corporate social responsibility (CSR) have an effect on firm value.